Knowledge sharing behavior among flood victims in Malaysia - Ahmad, Mazida; Mohamad Zani, Nurzawani; Hashim, Kamarul Faizal (Asian Research Publishing Network (ARPN), 2013)
During a disaster, knowledge sharing plays an important role in helping save lives, delivering immediate relief, supporting victims and minimizing the effect of the disaster.This study investigates the determinant factors of individuals’ knowledge-sharing intentions during a disaster. Social cognitive theory (SCT) is used as the underlying theory to predict victims’ knowledge-sharing behavior.This study used a survey as its data collection technique. The respondents were victims who had shared knowledge during a flood. The data was analyzed using structural equation modeling with SmartPLS. The findings show that self-efficacy, social support, and social recognition significantly influence knowledge-sharing intention. However, reciprocity was not found to significantly influence knowledge-sharing intention. The findings suggest the flood victims’ knowledge-sharing behaviors are strongly influenced by social recognition. Through this research, an initial conceptual model of the determinants of knowledge-sharing behavior is proposed.